Stability analysis of switched stochastic delay system with unstable subsystems. (November 2021) - Xiao, Hanni; Zhu, Quanxin
Abstract: This paper investigates the stability of switched stochastic delay systems (SSDSs) with unstable subsystems. By using the multiple Lyapunov–Krasovskii functionals (MLKFs) method combined with the mode-dependent average dwell time of stable subsystems (MDADTSS) and the mode-dependent average dwell time of unstable subsystems (MDADTUS) method, SSDSs with unstable subsystems are analyzed, and several novel sufficient conditions for finite-time stability and p th moment exponential stability are given. Compared with the existing related works, our work considers the influences of random disturbance and delays on the stability of SSDSs. Finally, we provide two examples to illustrate the feasibility of this method.